Improving the Stability of CsPbBr3 Perovskite Nanocrystals by Peroxides Post-treatment - Liu, Min; Li, Zhichun; Zheng, Weilin; Kong, Long; Li, Liang (Frontiers in Materials, 2019)
Metal oxides exhibit excellent barrier properties against moisture and oxygen, which are regarded as the powerful candidate for boosting the stability of perovskite nanocrystals (NCs). Here, we develop a simple method to coat perovskite NCs with PbO by peroxides post-treatment. Firstly, the didodecyl dimethyl ammonium sulfide (DDAS) was used to modify the CsPbBr3 NCs (DDAS-CsPbBr3), and then sequentially treated with benzoyl peroxide (BPO). By this way, the self-metal source (lead) can be easily oxidized, leading to the quick growth of lead oxide (PbO) on the surface of individual CsPbBr3 NCs. Under illumination with a 450 nm LED light (175mW/cm2), the PbO coated CsPbBr3 NCs maintained at approximately 90% of the initial intensity for 20 h of operations; in contrast, the emission from the CsPbBr3 NCs completely quenched.